Effect of the girth welding interpass temperature on the toughness of the HAZ of a Ni-based superalloy 625 clad API 5L X65 pipe welded joint - Diogo de Oliveira Moraes; Petrônio Zumpano Júnior; Victor Hugo Pereira Moraes e Oliveira; Aline Capella de Oliveira; João da Cruz Payão Filho (Journal of Materials Research and Technology, 2022)
Increasing the welding interpass temperature (IT) reduces the welding time and cost, particularly for offshore welding pipeline construction. However, it may degrade the mechanical properties of the welded joint; therefore, it is necessary to evaluate the effect of high IT on the heat-affected zone (HAZ). The influence of IT as high as 400 °C on the coarse-grained and intercritically reheated coarse-grained HAZs (CGHAZ and ICCGHAZ, respectively) of a Ni-based superalloy 625 (corrosion-resistant alloy UNS N06625) clad API 5 L X65 pipe was investigated. The joints were welded using a mechanized gas metal arc. The base metal (BM) and HAZ of the joints were evaluated using optical and scanning electron microscopy, as well as Vickers hardness, tensile strength, Charpy V-notch (CVN) at −30 °C, and crack tip opening displacement (CTOD) fracture toughness (−20 °C) testing. The CVN energy decreased as the IT increased from 300 to 400 °C owing to the formation of a large martensite-austenite-carbide (MAC) in the CGHAZ; however, all tests performed on joints welded at ITs up to 360 °C were considered acceptable based on DNVGL-ST-F101 requirements. The toughness results of the joint welded at an IT of 400 °C were not satisfactory, which indicates potential risks for the welding procedure qualification in this temperature range. Based on these findings, an increase in the IT up to 360 °C during gas metal arc welding (GMAW) using the adopted heat input is feasible. Moreover, this IT may be adopted for cost reduction because it decreases the total welding time by approximately 3 min per joint in the offshore welding of nickel-based superalloy 625 clad API 5 L X65 pipes.